Music and Imagination - Copland, Aaron 1900-1990 (Cambridge Harvard university press, 1980)
One of the most forthright and talented of American composers writes here of the part played by the freely imaginative mind in composing, performing, and listening to music. He urges more frequent performance and more sensitive hearing of the music of new composers. He discusses sound media, new and old, and looks toward a musical future in which the timbres and intensities developed by the electronic engineer may find their musical shape and meaning. He considers the twentieth-century revolt against classical form and tonality, and the recent disturbing political interference with the form and content of music. He analyzes American and contemporary European music and the flowering of specifically Western imagination in Villa-Lobos and Charles Ives.The final chapter is an account, partially autobiographical, of the composer who seeks to find, in an industrial society like that of the United States, justification for the life of art in the life about him. Mr. Copeland, whose spectacular success in arriving at a musical vernacular has brought him a wide audience, will acquire as many readers as he has listeners with this imaginatively written book.
The Charles Eliot Norton lectures 1951-1952
Keywords: Composing